Peran Pustakawan dalam Mengembangkan Inovasi Layanan Digital di Perpustakaan Universitas Bosowa - Hermawan, Nanang; Rahman, Idzhari; Surya Putri, Larasati Zuhro Nur Faizah; Mantasa, Kamaluddin (Literatify: Trends in Library Developments, 2025)
The Bosowa University Library has not yet been able to fully meet the overall information needs of library users regarding what they want at the Bosowa University Library. This research uses qualitative research, employing qualitative research methods by taking results from conclusions, which are based on the views obtained from respondents or participants. The ability of librarians to promote digital services in libraries makes it easier for users to meet their information needs in accordance with their requirements. Based on research results conducted on the use of digital services as a support for users' skills in information retrieval at Bosowa University Library, it is already very good, seeing the number of users who take advantage of the digital collections available in the library.The role of librarians is to educate users on how to use existing technology in information retrieval and research needs for the users